(untitled) (Global Journal of Medical Research, 2021)
A person having heaviness and bulkiness of the body due to extensive growth especially in Udaradi region is termed as "Sthula" and the state (Bhava) of Sthula is called "Sthaulya". Sthaulya or Medorog (obesity) is commonest metabolic disorders in affluent societies caused by irregular diet and sleep patterns, lack of physical activities, stress etc, and it is a direct result of modernization combined with lifestyle changes by exposing oneself to these factors. we unknowingly invited several diseases out of which Sthaulya is one which affects someone’s social, physical, and mental features. Acharya Charaka has mentioned Sthaulya under Santarpanajanya Vyadhi. The present study deals with all the details of Sthaulya according to ayurvedic classics and its preventive methods like Nidan Parivarjan, therapeutic management along with medicine, diet, Pathya and Apathya.